The Effect of Team Games Tournament (TGT) Learning Model Using Genially Snakes and Ladders on Students’ Economics Achievement - Wulan Suci Indah Sari; Zul Afdal (Jurnal Ecogen, 2025)
This research investigates the impact of the Team Games Tournament (TGT) cooperative model—integrated with a Genially-based snakes and ladders game—on students’ achievement in economics. Employing a quasi-experimental approach with a nonequivalent control group and purposive sampling, data were gathered through tests. Findings reveal that the TGT model supported by the educational game significantly enhances students’ performance in economics at SMAN 2 Lubuk Basung.